Intensitas Serangan Hama pada Anakan Tanaman Hutan di Persemaian Permanen Tumbang Nusa Kalimantan Tengah: Intensity of Pest Attacks on Forest Seedlings in The Permanent Nursery of Tumbang Nusa Central Kalimantan - Firdara, Eritha Kristiana; Pidjath, Chartina; Yosep, Yosep; Penyang, Penyang; Raskita, Raskita (HUTAN TROPIKA, 2025)
This study aims to identify the types, frequency, and intensity of pest attacks on seedlings in the Permanent Nursery, Tumbang Nusa, Central Kalimantan. Nurseries play a vital role in supporting the rehabilitation and conservation of tropical rainforests. Pest attacks on seedlings can reduce plant productivity, cause seedling shortages, and hinder growth, ultimately affecting the success of forest rehabilitation efforts. The research was conducted through field surveys and direct observations to identify the types of pests attacking the seedlings.The results showed that six types of pests (grasshoppers, bagworms, crickets, nettle caterpillars, bush snails, and armyworms) attacked forest seedlings (Shorea balangeran, Alstonia spatulata, Tengkawang, and Shorea leprosula) in the Permanent Nursery managed by the Watershed and Protected Forest Management Center (Balai Pengelolaan Daerah Aliran Sungai dan Hutan Lindung) in Tumbang Nusa. The highest percentage of pest attacks on seedlings in the nursery was observed in Shorea balangeran (grasshoppers, 56%), Shorea leprosula (grasshoppers, 37%), Tengkawang (crickets, 51%), and Alstonia spatulata (grasshoppers, 34%).The intensity of pest attacks on the four seedling types in the nursery ranged from low to high damage categories (6% - 17%). The highest pest attack intensity occurred in Shorea balangeran at 17% (grasshoppers), Shorea leprosula at 11% (crickets), Tengkawang at 16% (crickets), and Alstonia spatulata at 10% (grasshoppers, bush snails, and armyworms). This study highlights the importance of nursery management, including seedling selection, routine fertilization, and weekly insecticide spraying, to minimize pest attacks and maintain seedling quality.